PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN KRIPIK PAREBERKAH KRIPIK DI PURWOREJO (STIE Rajawali Purworejo, 2021)
This research aims to find out: whether there is a positive and significant influence between the marketing mix on purchasing decisions among consumers of Berkah Kripik pare chips in Purworejo. The data source uses a questionnaire. The population in this study were consumers of Berkah Kripik bitter gourd chips in Purworejo. The sampling technique used was purposive sampling. The sample used was 33 people. The data analysis techniques used are simple regression analysis, coefficient of determination, and t test. The results of simple linear regression analysis show a constant value of 1.302, meaning that if the marketing mix has a value of zero, then the purchasing decision will be 1.302 and the b value will be 0.682, meaning that if the marketing mix increases by one point then the purchasing decision will increase by 0.682. The results of the t test show that the t-value of the marketing mix is 10.771, and the t-table value is 1.692, meaning that partially the marketing mix has a positive and significant influence on purchasing decisions. Therefore, the alternative hypothesis (Ha) which states that there is a positive and significant influence between the marketing mix on purchasing decisions is accepted, and the null hypothesis (Ho) which states that there is no positive and significant influence between the marketing mix on purchasing decisions is rejected.